20.15.4 problem 4

Internal problem ID [3830]
Book : Differential equations and linear algebra, Stephen W. Goode and Scott A Annin. Fourth edition, 2015
Section : Chapter 9, First order linear systems. Section 9.3, page 598
Problem number : 4
Date solved : Monday, January 27, 2025 at 08:03:08 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=3 x_{1} \left (t \right )+x_{2} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=-x_{1} \left (t \right )+x_{2} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.023 (sec). Leaf size: 31

dsolve([diff(x__1(t),t)=3*x__1(t)+x__2(t),diff(x__2(t),t)=-x__1(t)+x__2(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= {\mathrm e}^{2 t} \left (c_{2} t +c_{1} \right ) \\ x_{2} \left (t \right ) &= -{\mathrm e}^{2 t} \left (c_{2} t +c_{1} -c_{2} \right ) \\ \end{align*}

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 42

DSolve[{D[x1[t],t]==3*x1[t]+x2[t],D[x2[t],t]==-x1[t]+x2[t]},{x1[t],x2[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to e^{2 t} (c_1 (t+1)+c_2 t) \\ \text {x2}(t)\to e^{2 t} (c_2-(c_1+c_2) t) \\ \end{align*}